Outcomes of Arthroscopic Capsular Release in the Beach-Chair Versus Lateral Decubitus Position: A Systematic Review - Houck, Darby A. (Orthop J Sports Med, 2019)
BACKGROUND: Arthroscopic capsular release (ACR) for the treatment of adhesive capsulitis of the shoulder can be performed in either the beach-chair (BC) or lateral decubitus (LD) position. PURPOSE: To determine the clinical outcomes and recurrence rates after ACR in the BC versus LD position. STUDY DESIGN: Systematic review; Level of evidence, 4. METHODS: A systematic review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines was performed by searching PubMed, Embase, and the Cochrane Library databases for studies reporting clinical outcomes of patients undergoing ACR in either the BC or LD position. All English-language literature from 1990 through 2017 reporting on clinical outcomes after ACR with a minimum 3-month follow-up were reviewed by 2 independent reviewers. Recurrence rates, range of motion (ROM) results, and patient-reported outcome (PRO) scores were collected. Study methodological quality was evaluated using the modified Coleman Methodology Score (MCMS). RESULTS: A total of 30 studies (3 level 1 evidence, 2 level 2 evidence, 4 level 3 evidence, 21 level 4 evidence) including 665 shoulders undergoing ACR in the BC position (38.1% male; mean age, 52.0 ± 3.9 years; mean follow-up, 35.4 ± 18.4 months) and 603 shoulders in the LD position (41.8% male; mean age, 53.0 ± 2.3 years; mean follow-up, 37.2 ± 16.8 months) were included. There were no significant differences in overall mean recurrence rates between groups (BC, 2.5%; LD, 2.4%; P = .81) or in any PRO scores between groups (P > .05). There were no significant differences in improvement in ROM between groups, including external rotation at the side (BC, 36.4°; LD, 42.8°; P = .91), forward flexion (BC, 64.4°; LD, 79.3°; P = .73), abduction (BC, 77.8°; LD, 81.5°; P = .82), or internal rotation in 90° of abduction (BC, 40.8°; LD, 45.5°; P = .70). Significantly more patients in the BC group (91.6%) underwent concomitant manipulation than in the LD group (63%) (P < .0001). There were significantly more patients with diabetes in the LD group (22.4%) versus the BC group (9.6%) (P < .0001). CONCLUSION: Low rates of recurrent shoulder stiffness and excellent improvements in ROM can be achieved after ACR in either the LD or BC position. Concomitant manipulation under anesthesia is performed more frequently in the BC position compared with the LD position.